A method for design of smoke control of urban traffic link tunnel (UTLT) using longitudinal ventilation. (April 2015) - Du, Tao; Yang, Dong; Peng, Shini; Xiao, Yimin
Graphical abstract: Highlights: We propose a simplified design method for smoke control of UTLT. Conversion of looped ventilation network to a branches one is achieved. The ventilation network of a UTLT is divided to three characterized regions. The deviations between the design and numerical simulation are small. Abstract: An urban traffic link tunnel (UTLT) typically consists of a looped main tunnel and several adjoining ramp tunnels. This complex network system creates a high level of fire risk and complicates smoke control. A generic design procedure to control the smoke flow in a UTLT with longitudinal forced ventilation is proposed in this paper with the relevant design criteria. The ventilation network in a UTLT is divided into three characterized regions: smoke discharge branches, smoke-prevention branches upstream of the fire and the smoke-prevention branches downstream of the fire. This conceptual division converts the looped ventilation network into a branched one, where a simple, one-dimensional calculation approach can be used to develop an appropriate ventilation system, and to solve the flow rates for the various branches. The ventilation system in a UTLT was determined using this novel design method, and the resultant flow rates for the key branches were compared to the steady-state solutions for a three-dimensional numerical simulation. The results demonstrate that the method proposed in this paper is a valid and efficient design tool for controlling smoke in UTLTs.